2021
DOI: 10.24272/j.issn.2095-8137.2020.334
|View full text |Cite
|
Sign up to set email alerts
|

Northern pig-tailed macaques (<i>Macaca leonina</i>) infected with SARS-CoV-2 show rapid viral clearance and persistent immune response

Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2), has become an unprecedented global health emergency. At present, SARS-CoV-2-infected nonhuman primates are considered the gold standard animal model for COVID-19 research. Here, we showed that northern pig-tailed macaques ( Macaca leonina , NPMs) supported SARS-CoV-2 replication. Furthermore, compared with rhesus macaques, NPMs showed rapid viral clearance in lung tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…These limitations can be counteracted by using animal models, although severe disease observed in humans cannot be completely recapitulated. Animals, including monkeys, tree shrews, and ferrets, are permissive to SARS-CoV-2 infection ( Deng et al, 2020 ; Fan et al, 2022 ; Kim et al, 2020 ; Muñoz-Fontela et al, 2020 ; Munster et al, 2020 ; Shan et al, 2020 ; Song et al, 2021 ; Song et al, 2020 ; Xu et al, 2020 ), with various animal models developed to test vaccines ( Gao et al, 2020 ; Wang et al, 2020b ) and understand disease progression and immune responses ( Lee et al, 2021 ; Nelson et al, 2022 ). Rhesus macaques are a commonly used non-human primate model for studies on human respiratory viral diseases ( Skinner et al, 2014 ; Yao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations can be counteracted by using animal models, although severe disease observed in humans cannot be completely recapitulated. Animals, including monkeys, tree shrews, and ferrets, are permissive to SARS-CoV-2 infection ( Deng et al, 2020 ; Fan et al, 2022 ; Kim et al, 2020 ; Muñoz-Fontela et al, 2020 ; Munster et al, 2020 ; Shan et al, 2020 ; Song et al, 2021 ; Song et al, 2020 ; Xu et al, 2020 ), with various animal models developed to test vaccines ( Gao et al, 2020 ; Wang et al, 2020b ) and understand disease progression and immune responses ( Lee et al, 2021 ; Nelson et al, 2022 ). Rhesus macaques are a commonly used non-human primate model for studies on human respiratory viral diseases ( Skinner et al, 2014 ; Yao et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these disease features are also relevant to severe COVID-19 disease [49][50][51][52][53][54][72][73][74] . A recent report demonstrated that a related species of pigtail macaques showed an abbreviated period of SARS-CoV-2 viral replication but possibly more severe disease than RhM 75 . Thus, PTM may be a reasonable model for severe disease and used to test novel therapeutics and vaccines to prevent disease.…”
Section: Discussionmentioning
confidence: 99%
“…PTM are also susceptible to influenza infection and show a strong persistent immune response to infection [83]. A recent report demonstrated that a related species of pigtail macaques (Macaca leonine) showed an abbreviated period of SARS-CoV-2 viral replication but possibly more severe disease than RhM [84]. Thus, PTM may be a reasonable model for severe disease and used to test novel therapeutics and vaccines to prevent disease.…”
Section: Plos Pathogensmentioning
confidence: 99%